Dacarbazine, Cisplatin, and Interferon-alfa-2b with or without Interleukin-2 in metastatic melanoma: a randomized phase III trial (18951) of the European Organisation for Research and Treatment of Cancer Melanoma Group - Keilholz, Ulrich; Schadendorf, Dirk (Journal of clinical oncology, 2016)
Background: Based on phase II trial results, chemoimmunotherapy combinations have become the preferred treatment for patients with metastatic melanoma in many institutions. This study was performed to determine whether interleukin-2 (IL-2) as a component of chemoimmunotherapy influences survival of patients with metastatic melanoma. Patients and Methods: Patients with advanced metastatic melanoma were randomly assigned to receive dacarbazine 250 mg/m2 and cisplatin 30 mg/m2 on days 1 to 3 combined with interferon-alfa-2b 10 × 106 U/m2 subcutaneously on days 1 through 5 without (arm A) or with (arm B) a high-dose intravenous decrescendo regimen of IL-2 on days 5 through 10 (18 × 106 U/m2/6 hours, 18 × 106 U/m2/12 hours, 18 × 106 U/m2/24 hours, and 4.5 × 106 U/m2 for 3 × 24 hours). Treatment cycles were repeated in the absence of disease progression every 28 days to a maximum of four cycles. Results: Three hundred sixty-three patients with advanced metastatic melanoma were accrued. The median survival was 9 months in both arms, with a 2-year survival rate of 12.9% and 17.6% in arms A and B, respectively (P = .32; hazard ratio, 0.90; 95% CI, 0.72 to 1.11). There was also no statistically significant difference regarding progression-free survival (median, 3.0 v 3.9 months) and response rate (22.8% v 20.8%). Conclusion: Despite its activity in melanoma as a single agent or in combination with interferon-alfa-2b, the chosen schedule of IL-2 added to the chemoimmunotherapy combination had no clinically relevant activity.
Elektronische Reproduktion der Druckausgabe
Gesehen am 22.01.2021